Existence result for a two-dimensional system of conservation laws with unilateral constraints. (July 2023) - Berthelin, F.
Abstract: The aim of this paper is to study a pressureless model with unilateral constraint in two dimensions. The corresponding one-dimensional case is a traffic flow model and was studied in Berthelin et al. (2008). The two-dimensional extension is linked to a pedestrian flow. Several challenges, geometric and analytical, appear with respect to the one-dimensional case. We get the existence of weak solutions for general initial data and the constraints taken in the strong sense.